2008
DOI: 10.1109/tps.2008.927138
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Spectrum Analysis of Welding Arc in Low-Power YAG-Laser–MAG Hybrid-Welding Process

Abstract: The behavior and emission spectrum of hybridwelding arc plasmas are investigated in low-power YAG lasermetal active gas (MAG) arc hybrid-welding process, comparing with simple MAG welding case. The electron temperature and electron density of local arc plasma, deducing, respectively, from the Boltzmann plot method and Stark broadening mechanism, are analyzed in this paper. The conditions of local thermodynamic equilibrium (LTE) of arc plasma and self-absorption of emission spectral lines are discussed. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…For example, the laser-arc interactions have been examined by noting increased arc stability and bending of the arc towards the laser generated keyhole. 1,18,41,56,135 However, the origin of the synergistic interaction that occurs between the arc and laser generated plasmas for various welding conditions is not well understood. Spectroscopic investigations of the optical emissions can provide a better understanding of the laser-arc interactions from the spatial and temporal distributions of electron temperatures and densities in the plasma for various welding conditions.…”
Section: Areas For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the laser-arc interactions have been examined by noting increased arc stability and bending of the arc towards the laser generated keyhole. 1,18,41,56,135 However, the origin of the synergistic interaction that occurs between the arc and laser generated plasmas for various welding conditions is not well understood. Spectroscopic investigations of the optical emissions can provide a better understanding of the laser-arc interactions from the spatial and temporal distributions of electron temperatures and densities in the plasma for various welding conditions.…”
Section: Areas For Future Researchmentioning
confidence: 99%
“…[1][2][3][4][5] As a result, hybrid welding produces weld pools that are wider than laser welds and deeper than arc welds made with the same laser and arc welding parameters respectively. [6][7][8][9][10][11][12][13][14][15][16][17][18] Differences in the weld geometries produced by autogenous laser, hybrid and arc welding are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Existing efforts have focused on proposing various phenomena that are measurable from the top side, including arc voltage [1,2] reflecting the distance from the electrode to the weld pool, surface of the weld pool [3][4][5][6][7] that produces the penetration, spectrum of the plasma [8][9][10] which contains vapour of elements from the melted workpiece, ultrasonic propagation in workpiece [11][12][13] that is influenced by the interface of the liquid pool with the melted material, infrared radiation [14][15][16] indicating the temperature distribution, and weld pool oscillation [17][18][19][20]. While certain correlations were demonstrated, no studies have claimed their adequacies.…”
Section: Introductionmentioning
confidence: 99%
“…2,[19][20][21] Recently, emission spectroscopy has been identified as a useful method for studying the GTAW arc plasma 22 and laser welding plasma 23 and has been applied to investigate arc plasma in laser arc hybrid welding. [24][25][26] Liu and Hao found that the hybrid arc plasma temperature decreased and the density increased compared with the conventional GTAW. 24 Ribic et al studied the electron temperature, electron density and electrical conductivity of the hybrid welding plasma for various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…26 Emission spectroscopy techniques were found to be a suitable method for investigating the interaction between laser and arc plasma in laser arc hybrid welding. [24][25][26] Laser arc hybrid welding is a complicated physical process where both the laser energy itself and the laser induced metal vapour or plasma plume simultaneously influence the arc plasma. 18,[24][25][26] It is therefore necessary to study the separate effects of the laser energy and laser induced metal vapour on the arc plasma.…”
Section: Introductionmentioning
confidence: 99%